Research progress in extracorporeal shock wave therapy for upper limb spasticity after stroke - Haoyang Duan; Yawen Lian; Yuling Jing; Jingsong Xing; Zhenlan Li (Frontiers in Neurology, 2023)
Spasticity is one of the most common complications after stroke. With the gradual intensification of spasticity, stroke patients will have a series of problems such as joint ankylosis and movement restriction, which affect the daily activities and increase the burden on patients' families, medical staff and society. There are many ways to treat post-stroke spasticity before, including physical therapy and exercise therapy, drug therapy, surgery and so on, but not satisfied because of a few shortcomings. In recent years, many researchers have applied extracorporeal shock wave therapy (ESWT) for the treatment of post-stroke spasm and achieved good clinical effect, because it is non-invasive, safe, easy to operate, low cost and other advantages compared with other treatment methods. This article reviews the research progress and existing problems of ESWT in the treatment of post-stroke spasticity.